2021
DOI: 10.1371/journal.pgen.1009888
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GSTu1-mediated insecticide resistance in Plutella xylostella by miRNA and lncRNA

Abstract: The evolution of resistance to insecticides is well known to be closely associated with the overexpression of detoxifying enzymes. Although the role of glutathione S-transferase (GST) genes in insecticide resistance has been widely reported, the underlying regulatory mechanisms are poorly understood. Here, one GST gene (GSTu1) and its antisense transcript (lnc-GSTu1-AS) were identified and cloned, and both of them were upregulated in several chlorantraniliprole-resistant Plutella xylostella populations. GSTu1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 63 publications
(73 reference statements)
1
48
0
Order By: Relevance
“…One P. xylostella GST, GSTu1 upregulated in several chlorantraniliprole-resistant P. xylostella strains was confirmed to contribute to chlorantraniliprole resistance 115 . In that study, GSTu1 was suggested to be regulated by a novel noncoding RNA-mediated pathway 115 . In Locusta migratoria , LmGSTE4 was found to metabolize malathion and DDT.…”
Section: Functions Of Insect Gsts In Host Plant Adaptation and Pestic...mentioning
confidence: 82%
See 1 more Smart Citation
“…One P. xylostella GST, GSTu1 upregulated in several chlorantraniliprole-resistant P. xylostella strains was confirmed to contribute to chlorantraniliprole resistance 115 . In that study, GSTu1 was suggested to be regulated by a novel noncoding RNA-mediated pathway 115 . In Locusta migratoria , LmGSTE4 was found to metabolize malathion and DDT.…”
Section: Functions Of Insect Gsts In Host Plant Adaptation and Pestic...mentioning
confidence: 82%
“…Recently, RNAi-mediated knockdown of four overexpressed GST genes in the imidacloprid resistant N. lugens resulted in increased sensitivities to the insecticide, suggesting the roles of these GSTs in imidacloprid resistance of N. lugens [114]. One P. xylostella GST, GSTu1 upregulated in several chlorantraniliprole-resistant P. xylostella strains was confirmed to contribute to chlorantraniliprole resistance [115]. In that study, GSTu1 was suggested to be regulated by a novel noncoding RNA-mediated pathway [115].…”
Section: Functions Of Insect Gsts In Host Plant Adaptation and Pestic...mentioning
confidence: 88%
“…Advancements in high-throughput techniques have enabled researchers to identify lncRNAs in various insect species, such as D. melanogaster [ 13 ], B. mori [ 57 ], A. mellifera [ 23 ], Anopheles gambiae [ 58 ], Aedes aegypti [ 59 ], and Nilopervata lugens [ 60 ]. In P. xylostella , a few lncRNA studies have been performed [ 61 ], but most focus on exploring the role of lncRNAs in insecticide resistance [ 51 , 62 , 63 , 64 ]. Several studies have been conducted in P. xylostella investigating the role of miRNAs-mRNAs in response to pathogenic fungus infection [ 35 , 54 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the global population expands, it is necessary to satisfy an increasing demand for crops. Pests can cause serious decreases in horticulture and agriculture crop yield and quality, threatening worldwide food security, and insecticides are essential to protect crops from pests in modern agriculture. , Nevertheless, the long-term widespread application of older chemical insecticides has led to serious environmental risks and persistent insect resistance issues for integrated pest management (IPM). The typical example is Plutella xylostella, one of the most destructive insect pests for Brassicaceae crops, which has developed resistance to about 100 insecticides. Therefore, it is urgent to develop environmentally benign insecticides with high efficiency, low toxicity, and novel modes of action. , …”
Section: Introductionmentioning
confidence: 99%